Development of Employee Letter Administration System at PT. Anugrah Laut Indonesia (ALI Seafood) - Rahmawati, Dewi; Ananda, Dahliar; Kristanto, Titus (Abdi Masyarakat, 2024)
PT. Ali Seafood Indonesia is a company engaged in the production and trade of marine products. In this company, Personnel Letter Administration is one of the activities that has an important role in an organization. The process of submitting, creating, disseminating and filing letter artifacts can be done as much as possible to simplify the work of the Human Resources unit. PT. Anugrah Laut Indonesia (ALI Seafood) which is engaged in the production and trade of marine products also has the same needs in handling these needs. With the number of employees that has reached approximately 200 workers, of course a model for managing personnel letter administration is needed that can help the Human Resources Unit in its operations. The problem that occurs at ALI Seafood is the need for a computerized application that can be used to manage personnel letter administration that is integrated with the existing human resources system. The current condition has been implemented for several types of letters, but development is still needed for several other types of letters. The S1 Software Engineering study program collaborates with ALI Seafood in developing the application in an activity summarized in the community service activity "Implementation of the application for administering employee letters at PT. Anugrah Laut Indonesia". The target output of this activity is the existence of an application for managing employee letters and journals published by national proceedings or national journals.